MINORITAS MUSLIM DI AUSTRALIA DAN INGGRIS - Kartini, Indriana (Pusat Penelitian Politik, 2006)
The war against terrorism has become the main topic and spread a ll over the w orld since the bombing o f WTC building in September 11